Balance and perspectives of the victimization studies in Colombia: hidden and complained real crime. - Quintero Ángel, David (Sociedad y Economía, 2010)
This paper is a review of major studies on the theme of victimization that have been conducted in Colombia since 1985. Also, an analysis of the real crime, hidden and complained to the city of Cali, from victimization survey DANE 2003. This is to show that not all sectors of society are affected by crime in the same way: the lower strata are the most victimized and the most vulnerable, while the high seems to live in a much better position, in many cases because of private protection. Finally, some methodological findings contribute to future studies.